Health-related quality of life and its association with socioeconomic status and diet diversity in Chinese older adults - Zhang, Chichen; Zhang, Jiachi; Xiao, Shujuan; Shi, Lei; Xue, Yaqing; Zheng, Xiao; Benli, Xue; Chen, Yiming; Li, Xinru; Kai, Yan; Liu, Yuxi; Zhou, Guangqing (Frontiers in Public Health, 2023)
Objectives The study aimed at examining the combined association of socioeconomic status (SES) and diet diversity (DD) with health-related quality of life (HRQoL) and exploring whether DD played a mediating role in the relationship between varied SES and HRQoL among Chinese older persons. Method A multi-stage random sampling method was conducted in Shanxi Province of China, with 3,250 older adults participating in this cross-sectional survey. SES was divided into groups by quartiles and DD by means, and these variable groups were combined in pairs to generate a total of eight combinations. The PROCESS macro developed by Hayes was employed for the simple mediation analysis. Results Compared with the reference group (those with both high SES and high DD), older adults who were classified to have lower SES or DD had elevated odds of having worse HRQoL: low SES/ low DD (OR = 1.65, 95% CI 1.41–2.92); low SES/ high DD (OR = 1.45, 95% CI 1.17–1.80); middle low SES/ low DD (OR = 1.43, 95% CI 1.24–1.65); middle low SES/ high DD (OR = 1.23, 95% CI 1.03–1.47); upper high SES/ low DD (OR = 1.41, 95% CI 1.21–1.65); and high SES/ low DD (OR = 1.30, 95%CI 1.10–1.53). The mediation analysis revealed that DD mediated the relationship between SES and HRQoL (B=0.011, 95% CI 0.008–0.013), with its indirect effects accounting for 39.29% of the total effects. Conclusions These findings highlighted the role of DD as a mediator of the relationship between SES and HRQoL. As DD could be protective, modifiable, and easy for older adults to understand and implement, village clinics and community health stations should work collaboratively to design proper DD intervention measures for better HRQoL.